Pemartabatan Bahasa Indonesia di Perguruan Tinggi Keagamaan Islam Negeri (PTKIN) se-Jawa dan Madura - Muyassaroh; Siti Zumrotul Maulida; Aldila Rahmita Putri; Dita Karisma Fahriani (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
Eksistensi bahasa Indonesia di kancah dunia perlu didukung dengan meningkatkan martabat bahasa Indonesia. Pemartabatan bahasa Indonesia dapat dilakukan melalui internalisasi dan internasionalisasi bahasa Indonesia melalui Perguruan Tinggi Keagamaan Islam Negeri (PTKIN) se-Jawa Madura. This State Islamic Religious College has succeeded in organizing the BIPA program as an effort to dignify the Indonesian language. Through the BIPA program, students are equipped with a good and correct understanding and use of Indonesian language. This research aims to describe the dignity of the Indonesian language and the implementation of BIPA learning in PTKIN throughout Java and Madura. The method used in this research is qualitative with a case study design. The data source for this research is the implementation of the BIPA program at PTKINs throughout Java and Madura which have the Indonesian Tadris study program. The data obtained was then analyzed using interactive data analysis. The results of the research show that the BIPA program has been implemented by all PTKIN throughout Madura Java and is presented in specialization courses in the Indonesian Language Tadris Study Program. Through the BIPA program, foreign students studying at PTKIN are trained their Indonesian language skills in the matriculation program before entering college.